A Government Sponsored Clinic for the Evaluation and Treatment of Chronic Hepatitis C in an Underinsured Population in Puerto Rico - Costas, Pablo; Ortiz, Adelaida; Velázquez, Vanessa; Torres, Esther A. (Puerto Rico Health Sciences Journal, 2013)
Background: Chronic hepatitis C (CHC) is a major health problem in Puerto Rico (PR). More than 50% of the population is insured by a government-sponsored managed care system that does not cover treatment for CHC. Lack of access to treatment will result in an increase in end-stage liver disease with its high socioeconomic impact in the future. In an attempt to identify strategies for the treatment of CHC in the publicly insured population, the PR Health Department and the University of Puerto Rico (UPR) Gastroenterology (GI) Division have developed a pilot clinic for the evaluation and treatment of CHC. Methods: UPR and the PR Health Department negotiated a fee per patient to include all medical care and follow-up laboratories. Viral studies were covered by a grant to the Health Department Medications were bought at a discount price by the government and dispensed at a government pharmacy. The Health Department allocated funds for 200 patients with government insurance. A dedicated clinic was established at the UPR, staffed by an internist under the supervision of the GI faculty. Patients with a positive HCVab were referred to this clinic. The public insurance covered the CBC, liver tests, metabolic panel, TSH, HBsAg, HIV, ultrasound and liver biopsy, which were required prior to evaluation for possible treatment. In the initial visit, patients underwent a medical evaluation, including assessment of suitability for therapy and counseling. Those deemed to be candidates who still needed a liver biopsy had it performed by the GI staff. Genotype and viral titers were ordered after the decision on treatment had been made. The clinic physician prescribed pegylated interferon and ribavirin, which were dispensed by the government pharmacy. Instruction on proper drug administration was given. Clinic visits were scheduled for 1, 3, 6 and 12 months but also allowed on demand. Laboratory tests were done at the clinic and reviewed by the physician expediently to monitor for toxicity. Any medical problems or treatment for complications of therapy were covered by the primary insurer. Viral load was repeated at 12 weeks to discontinue therapy in those unlikely to respond. The budget per patient for medical visits and laboratory tests was $1,500.00, HCV RNA titers plus genotype costs $200.00, and HCV qualitative RNA costs $123.00 Results: 405 patients have been referred between February 2002 and April 2003 (the number was increased at adjust for no-shows and those not treated). 30% are female, the major risk factor is IVDU, and 80% are unemployed. 101 have started treatment and 48 are awaiting biopsy. A support group has been established at the clinic. Conclusions: The treatment for CHC in practice is not only costly but also resource consuming. Most gastroenterologists in our community refer these patients for treatment. The establishment of a dedicated clinic with a primary physician supervised by the specialists reduces costs and facilitates caring for a larger number of patients. The volume of services allows for negotiation of medical, laboratory and drug costs. In allocating funds for this project, the PR Health Department recognized the importance in reducing the potential spread in the community by treating infected patients as well as reducing the future medical and socioeconomic burden of end-stage liver disease. Although the outcome of this project is still unseen, we believe that this model may serve to establish other clinics for the treatment of CHC at lower costs with the same effectiveness.